2002
DOI: 10.1039/b110449g
|View full text |Cite
|
Sign up to set email alerts
|

Cascade chemistry in azacryptand cages: bridging carbonates and methylcarbonatesElectronic supplementary information (ESI) available: magnetic data. See http://www.rsc.org/suppdata/dt/b1/b110449g/

Abstract: The different tendencies of dinuclear azacryptates of the m-CH 2 C 6 H 4 CH 2 and 2,5-furano-spaced hosts L 1 and L 2 to catalyse CO 2 uptake-reactions within these sterically-protected host cavities are examined. Bridging methylcarbonates are generated catalytically upon exposure of methanol solutions of L 1 , but not L 2 , di-transition cation cryptates to atmospheric CO 2 . X-Ray crystallographic structures of homodinuclear µ-carbonato cryptates of both ligands and µ-methylcarbonato cryptates of L 1 with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 32 publications
6
94
0
2
Order By: Relevance
“…The electronic density was analysed using the natural bond orbital (NBO) technique [39]. To estimate the energetic effects of a methanolic medium, as used experimentally for the fixation process [4,5], solvation effects were calculated at the B3LYP/6-311++ G(2d,2p) level using the universal solvent model, SMD [40].…”
Section: Computational Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The electronic density was analysed using the natural bond orbital (NBO) technique [39]. To estimate the energetic effects of a methanolic medium, as used experimentally for the fixation process [4,5], solvation effects were calculated at the B3LYP/6-311++ G(2d,2p) level using the universal solvent model, SMD [40].…”
Section: Computational Methodologymentioning
confidence: 99%
“…Previous work has shown that, in the presence of appropriate ligand environments and electron-rich metal centres, the reduction of CO 2 is possible, producing carbonates, oxalates, for example [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. A variety of transition metal complexes with M-OR fragments undergo insertion reactions with CO 2 [4,6,7,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early indications of such enhanced reactivity have been manifest by insertion of methanol into the carbonato-bound azacrytates, forming a methyl carbonato bridged complex. [20] This demonstrates activation of the bound carbonate towards nucleophilic attack which we have attempted to exploit in this work by using these complexes as CO 2 reduction catalysts. When these complexes have been used as homogeneous catalysts in the CO 2 + H 2 reaction minor mounts of formic acid and methanol have been noted as products.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Azacryptate complexes containing pairs of metal ions from the first transition metal series have been shown to take up CO 2 spontaneously from the atmosphere. [20,21] This process occurs in a wet solvent system and the CO 2 is fixed as a carbonate bridge between the metal centres.…”
Section: Introductionmentioning
confidence: 99%